Analysis of Optimizing Budget Refocusing for Efficiency in The Department of Industry Trade Energy and Mineral Resources of North Sumatra Province - Agustin, Putri Dianita; Ramadhan, Puja Rizqy; Nasution, Anggi Pratama (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2026)
This study analyzes the strategy of budget refocusing optimization and its implications for efficiency and program performance at the Department of Industry, Trade, Energy, and Mineral Resources of North Sumatra Province. A qualitative case study approach was employed. Primary data were collected through in-depth interviews with three civil servants from the planning, finance, and domestic trade development divisions, while secondary data were obtained from budget realization reports up to the second quarter of the 2025 fiscal year. Data were analyzed using thematic analysis supported by NVivo 15. The findings indicate that budget refocusing in the 2025 fiscal year was conducted under limited fiscal space and influenced by changes in national and regional policy directions, resulting in a predominantly reactive strategy and low budget realization, particularly in capital expenditure. Nevertheless, a shift toward outcome-oriented budget management was identified, emphasizing the importance of strengthening strategic planning and performance-based evaluation to enhance efficiency and accountability in local public financial governance.